Molecular cloning of Bacillus sphaericus penicillin V amidase gene and its expression in Escherichia coli and Bacillus subtilis. - Olsson, A (1985)
The Bacillus sphaericus gene coding for penicillin V amidase, which catalyzes the hydrolysis of penicillin V to yield 6-aminopenicillanic acid and phenoxyacetic acid, has been isolated by molecular cloning in Escherichia coli. The gene is contained within a 2.2-kilobase HindIII-PstI fragment and is expressed when transferred into E. coli and Bacillus subtilis. The expression in B. subtilis carrying the recombinant plasmid is approximately two times higher than in the original B. sphaericus strain. A comparison of the purified enzyme from B. sphaericus and the expressed gene product in E. coli minicells suggests that the native enzyme consists of four identical subunits, each with a molecular weight of 35,000.